2021
DOI: 10.1002/pip.3459
|View full text |Cite
|
Sign up to set email alerts
|

Firing stability of tube furnace‐annealed n‐type poly‐Si on oxide junctions

Abstract: Stability of the passivation quality of poly-Si on oxide junctions against the conventional mainstream high-temperature screen-print firing processes is highly desirable and also expected since the poly-Si on oxide preparation occurs at higher temperatures and for longer durations than firing. We measure recombination current densities (J 0 ) and interface state densities (D it ) of symmetrical samples with n-type poly-Si contacts before and after firing. Samples without a capping dielectric layer show a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
(107 reference statements)
2
17
0
Order By: Relevance
“…However, firing of POLO junctions without any degradation is even possible at low firing belt velocities, which can make additional H supply unnecessary. [ 18 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, firing of POLO junctions without any degradation is even possible at low firing belt velocities, which can make additional H supply unnecessary. [ 18 ]…”
Section: Methodsmentioning
confidence: 99%
“…However, firing of POLO junctions without any degradation is even possible at low firing belt velocities, which can make additional H supply unnecessary. [18] After local ablation of the passivation stack on the rear side using a laser with 532 nm wavelength and pulses in the picosecond range, we screen print Al fingers on top of the laser contact openings. The wafers are fired in a conveyor belt furnace at 810 C set point temperature with a belt speed of 7.2 m min À1 .…”
Section: Bottom Cell Processing and Bottom Cell Characterizationmentioning
confidence: 99%
“…The detrimental impact of increasing the effective thermal budget of firing on the interface quality is in good agreement with observations made by Hollemann et al in a study published recently. 21 However, we note that in this study, they performed the firing step after previous activation of the poly-Si contact through a long-annealing step, whereas in the present study, the firing step was performed directly after deposition of the a-SiC x layer.…”
Section: Discussionmentioning
confidence: 86%
“…Peak temperature is only one component of the thermal profile. Several recent studies reported the degradation of the surface passivation of the poly-Si contact after firing (i.e., high-temperature thermal process featuring fast heating and cooling rates), suggesting that the thermal profile to which the poly-Si/SiO x contact is submitted strongly impacts its final structural and functional properties. , In the following, we discuss our current understanding of the effects of the heating ramp rate, dwell time, and overall thermal budget by comparing samples annealed in different setups as described in detail in the experimental section (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation